2021
DOI: 10.1152/ajpgi.00013.2021
|View full text |Cite
|
Sign up to set email alerts
|

Heartburn sensation in nonerosive reflux disease: pattern of superficial sensory nerves expressing TRPV1 and epithelial cells expressing ASIC3 receptors

Abstract: The underlying causes of heartburn, characteristic symptom of gastro-esophageal reflux disease(GERD), remain incompletely understood. Superficial afferent innervation of the esophageal mucosa in nonerosive reflux disease(NERD) may drive nociceptive reflux perception, but its acid-sensing role has not yet been established. Transient receptor potential vanilloid subfamily member-1(TRPV1), transient receptor potential Melastatin 8(TRPM8), and acid sensing ion channel 3(ASIC3) are regulators of sensory nerve activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…In mammals, chemosensors such as ASIC and transient receptor potential channels (e.g. TRPV1) are expressed in sensory neurons innervating the gastrointestinal tract [17], but oesophageal, intestinal, and lung epithelial cells also express ASICs, potentially contributing to acid-induced secretions, transport, and inflammation [6870]. The gastrointestinal expression of ASICs may reflect a chemosensory role, like that mediated by ASICs in neurons innervating the lungs and skin of mammals [71, 72].…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, chemosensors such as ASIC and transient receptor potential channels (e.g. TRPV1) are expressed in sensory neurons innervating the gastrointestinal tract [17], but oesophageal, intestinal, and lung epithelial cells also express ASICs, potentially contributing to acid-induced secretions, transport, and inflammation [6870]. The gastrointestinal expression of ASICs may reflect a chemosensory role, like that mediated by ASICs in neurons innervating the lungs and skin of mammals [71, 72].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, our recent study showed that TRPV1 is frequently expressed on superficial afferent nerves in the esophageal epithelium whereas occasional expression was seen on deep nerves around basal layer. 62 On the other hand, a randomized controlled study by Krarup et al 63 showed no inhibitory effect of TRPV1 antagonist on chest pain induced by heat, distension or electronic current in the esophagus. With regard to other TRPs receptors, transient receptor potential melastatin 8 (TRPM8) might be involved in esophageal hypersensitivity as menthol (i.e., TRPM8 agonists) infusion into the esophagus triggers different sensation in healthy subjects (cold sensation) and GERD patients (heartburn).…”
Section: Sensory Receptors (Trpv1 and Asic3)mentioning
confidence: 98%
“…When esophageal sensory nerve endings are stimulated by chemical, mechanical, temperature, or pressure changes, the expression of these acid-sensitive receptors also changes accordingly and further affects the release of neurotransmitters or changes in the electrophysiology of the esophageal mucosa. This results in potential inflammation, immunity, hyperalgesia, and NERD VH (Table 1) [13,[16][17][18][19][20][21].…”
Section: Nerd and The Activation Of Acid-sensitive Receptorsmentioning
confidence: 99%